Remineralising Effects of L-arginine Fluoride Mouthwash versus Sodium Fluoride Mouthwash: A Protocol of an In-vitro Study - Anjori Ajinkya Raut; Punit Ratnakar Fulzele (Journal of Clinical and Diagnostic Research)
Introduction: Preventing dental caries and maintaining oral health are important for children’s quality of life, as they profoundly impact overall well being, self-esteem and long-term health outcomes. Despite breakthroughs in preventive dentistry, oral infections and tooth decay remain common among children, highlighting the need for novel and efficient preventive interventions. Although fluoride is a proven preventive measure against tooth decay, L-arginine, a naturally occurring amino acid, has shown promising results in enhancing remineralisation and has gained interest due to its role in maintaining oral health. The combination of L-arginine and fluoride in mouthwash may improve dental health. Need of the Study: L-arginine fluoride is utilised in oral care products such as varnishes and toothpastes; however, there are no studies examining the efficacy of L-arginine fluoride as a mouthwash. Aim: To assess the remineralising activity of L-arginine fluoride mouthwash compared to sodium fluoride mouthwash. Materials and Methods: The present in-vitro study will be conducted in the Department of Paediatric and Preventive Dentistry, Sharad Pawar Dental College, Wardha, Maharashtra, India from September 2024 to December 2025. Forty-two teeth with no white spot lesions or caries will be included, while teeth with lesions, fractures, or wear will be excluded from the study. The teeth will be randomly divided into six groups with different concentrations of L-arginine fluoride, and a control group with sodium fluoride will also be evaluated. The teeth will be assessed for Ca/P ratio using Scanning Electron Microscopy with Energy Dispersive X-ray (SEM-EDX), mineral density using micro-Computed Tomography (micro-CT), and for mineral gain and remineralisation using a specific formula. The data will be statistically analysed using Statistical Package for Social Sciences (SPSS) software version 22.0; a two-way Analysis of Variance (ANOVA) with Bonferroni post-hoc test, a one-way ANOVA with Student-Newman-Keuls (SNK) test, and Kruskal-Wallis one-way ANOVA will be used. A p-value of <0.05 will be considered statistically significant.